Brain Cytochrome P450: Navigating Neurological Health and Metabolic Regulation - Pradeepraj Durairaj; Zixiang Leonardo Liu (Journal of Xenobiotics)
Human cytochrome P450 (CYP) enzymes in the brain represent a crucial frontier in neuroscience, with far-reaching implications for drug detoxification, cellular metabolism, and the progression of neurodegenerative diseases. The brain’s complex architecture, composed of interconnected cell types and receptors, drives unique neuronal signaling pathways, modulates enzyme functions, and leads to distinct CYP gene expression and regulation patterns compared to the liver. Despite their relatively low levels of expression, brain CYPs exert significant influence on drug responses, neurotoxin susceptibility, behavior, and neurological disease risk. These enzymes are essential for maintaining brain homeostasis, mediating cholesterol turnover, and synthesizing and metabolizing neurochemicals, neurosteroids, and neurotransmitters. Moreover, they are key participants in oxidative stress responses, neuroprotection, and the regulation of inflammation. In addition to their roles in metabolizing psychotropic drugs, substances of abuse, and endogenous compounds, brain CYPs impact drug efficacy, safety, and resistance, underscoring their importance beyond traditional drug metabolism. Their involvement in critical physiological processes also links them to neuroprotection, with significant implications for the onset and progression of neurodegenerative diseases. Understanding the roles of cerebral CYP enzymes is vital for advancing neuroprotective strategies, personalizing treatments for brain disorders, and developing CNS-targeting therapeutics. This review explores the emerging roles of CYP enzymes, particularly those within the CYP1–3 and CYP46 families, highlighting their functional diversity and the pathological consequences of their dysregulation on neurological health. It also examines the potential of cerebral CYP-based biomarkers to improve the diagnosis and treatment of neurodegenerative disorders, offering new avenues for therapeutic innovation.